How Cardinal Utility Entered Economic Analysis, 1909-1944 - Ivan Moscati (Duke University, Center for the History of Political Economy (CHOPE), 2013)
This paper illustrates the methodological and analytical issues that characterized, as well as the personal and institutional aspects that informed the discussions leading to the definition of the current notion of cardinal utility as utility unique up to positive linear transformations. As originally this type of utility was not called "cardinal", the paper also investigates the terminological question of when and how the expression "cardinal" was coupled with positive linear transformations. In opposition to existing narratives, the paper shows that cardinal utility entered economic analysis between 1909 and 1944, that is, during the ordinal revolution in utility theory.
Keywords: 330; Cardinal utility; Ranking of transitions; Differences of utility; Ordinal revolution; Paul Samuelson